The relationship between rainfall characteristic and total suspended solid (TSS) of stormwater in UMP Gambang - Noor Farahazwani, Che Noh (2017)
Stormwater runoff is a leading contributor to pollution in streams, rivers, and lakes in nationwide. It is because stormwater runoff contains pollutants from many different sources, decreasing pollution from stormwater runoff is a challenging task It requires cooperation from residents, businesses, and municipalities. An important step in protecting streams from stormwater pollution is understanding watershed processes, stormwater characteristics, and their combined effects on streams and water quality. The objective of the study was analysis relationship between rainfall characteristic and Total Suspended Solid (TSS) at UMP Gambang. The data was collected in September until November 2016.The Portable Water Smnple used to collect data of Total Suspended Solid (TSS), meanwhile equipment Rain Gauge was collected rainfall depth. The result in September has three events, October has eight events and in November has three events. The stormwater runoff relationship between rainfall intensities can be characterized in period out of rainless cause the lowest sedimentation